Features of using digital technologies at industrial enterprises in the region - Muhammadieva Yulduz Yusupovna (THE INNOVATION ECONOMY, 2026)
This article describes the essence of the digital transformation process, the strategy for implementing this process in the activities of enterprises and ways to implement this strategy, the grouping of digital technologies, the advantages and possible losses from the introduction of these technologies, the stages and models of the implementation of a digital enterprise.